The role of civil servants in the dignification of victims in Meta, Colombia. - Rios Oyola, Sandra M.; Hormaza, Carolina (Third World Quarterly, 2023)
Dignification of victims is understood as the process of restoring their dignity, which is their full and equal status as human beings with autonomy and material, social and natural conditions for a good or dignified life. We discuss how civil servants' understanding of a dignified victim affects how they implement material reparations. In turn, we explore how the implementation of material reparation affects the dignification of victims, according to victims. Using a life-story approach, we conducted 13 semi-structured interviews with civil servants and victims' leaders. This sample allowed us to analyse a cumulation of over 20 years of dedicated work with victims in the region. We identified four themes that civil servants consider necessary for a process of victim dignification: participation, empowerment, de-stigmatisation and dignified listening. We explain how these themes can have the non-intended consequence of ignoring or denying some important elements for the recognition of victims' dignity.